1992
DOI: 10.1083/jcb.116.4.989
|View full text |Cite
|
Sign up to set email alerts
|

Molecular organization of the uvomorulin-catenin complex.

Abstract: Abstract. The Cal+-dependent cell adhesion molecule uvomorulin is a member of the cadherin gene family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
227
0
2

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(239 citation statements)
references
References 26 publications
10
227
0
2
Order By: Relevance
“…These data are in excellent agreement with the results presented in Figure 5. Ozawa and Kemler, 1992; briefly reviewed by Takiechi, 1991). While the cytoskeletal network of mammalian Sertoli cells has been well-described and is known to consist in part of extensive and localized bundles of actin filaments closely apposed to both tight junctions and another form of cell-cell adhesion, the ectoplasmic specialization (Vogl et al, 1986), the expression of catenins in Sertoli cells remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in excellent agreement with the results presented in Figure 5. Ozawa and Kemler, 1992; briefly reviewed by Takiechi, 1991). While the cytoskeletal network of mammalian Sertoli cells has been well-described and is known to consist in part of extensive and localized bundles of actin filaments closely apposed to both tight junctions and another form of cell-cell adhesion, the ectoplasmic specialization (Vogl et al, 1986), the expression of catenins in Sertoli cells remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…1). Interactions between epithelial cells are stabilized by linkage of cadherin-catenin complexes to the cortical actin network in adherens junctions (Ozawa and Kemler, 1992), and transient or permanent inactivation of adherens junction complexes is required for cell migration/ invasion (Birchmeier and Behrens, 1994;Takeichi, 1993). The establishment of a cortical actin filament network is necessary for localization of cadherincatenin complexes at adherens junctions in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that cadherin proteins synthesized in 3D2.26 cells were unstable and proteolytically degraded. On the other hand, the levels of ␤-catenin, a cytoplasmic protein that links cadherin receptors to the actin cytoskeleton through its interaction with ␣-catenin in adherens junctions (Ozawa and Kemler, 1992), were unchanged in the transfectants (Fig. 3B), and ␤-catenin served as an internal protein loading marker.…”
Section: Scholl Et Almentioning
confidence: 99%
“…E-cadherin binds ␤-catenin in a 1:1 stoichiometric complex (Ozawa and Kemler, 1992;Huber and Weis, 2001). Therefore, one explanation for ␤-catenin stability and for its continued peripheral localization in E-cadherin depleted cells is that E-cadherin exists in large excess over ␤-catenin, and the reduction in E-cadherin by RNAi would then be insufficient to disrupt the complex.…”
Section: E-cadherin-␤-catenin Complex Is Disrupted In E-cadherin Knocmentioning
confidence: 99%